Noncovalent and nonspecific molecular interactions of polymers with multiwalled carbon nanotubes - Baskaran, Durairaj; Mays, Jimmy W.; Bratcher, Matthew S. (Chemistry of Materials, 2005)
Polymer composites containing variable amounts of multiwalled carbon nanotubes (MWNTs) have been prepared using solution dispersion and melt-shear mixing. Various polymer composites with 1 wt % MWNTs have been found to dissolve homogeneously in organic solvents. The amount of polymer coated or wrapped MWNTs dissolved in the solution was quantified using UV-vis absorbance at 500 nm and the concentration ratio of [MWNTs](solution)/[MWNTs](composite) was close to 1. A nonspecific polymer adsorption through multiple-weak molecular interactions of CH groups with MWNTs in the composites has been identified through FTIR spectroscopy. The composites of polybutadiene with different wt % of MWNTs showed slight changes in the CH bending vibrations, indicating the presence of intermolecular CH-pi interactions. The dissolution of various polymer composites containing low concentration of MWNTs in organic solvents was attributed to polymer coating on the MWNTs via noncovalent and nonspecific CH-pi interactions. The dissolution of MWNTs in organic solvents using common polymers used in this study indicates that the coating or wrapping is a general phenomenon occurring between polymers and carbon nanotubes.

Grafting reactions of living macroanions with multi-walled carbon nanotubes - Baskaran, Durairaj; Sakellariou, Georgios; Mays, Jimmy W.; Bratcher, Matthew S. (Journal of Nanoscience and Nanotechnology, 2007)
Grafting reactions of living polystyryllithium (PSLi) with acid chloride containing multi-walled carbon nanotubes (MWNTs-COCl) were performed under vacuum in benzene at room temperature. Covalent grafting of polystyrene (PS) was characterized using spectroscopic, microscopic, and thermogravimetric analyses. Grafting at different ratios of macroanion to acylchloride of the carbon nanotubes showed that the grafting efficiency was not dependent on the concentration of the macroanions. The mole percent of PS present in the MWNTs-g-PS samples was inversely proportional to the precursor molecular weight of PSLi. Direct reactions of PSLi, polybutadienyllithium and n-butyllithium with pristine MWNTs without any functional groups were also performed in the presence and in the absence of tetrahydrofuran in benzene. The grafting reactions of living macroanions either with MWNTs-COCl or with pristine MWNTs indicated a partial grafting of polymer on the carbon nanotubes in benzene at room temperature.
Keywords: Anionic polymerization; covalent functionalization; grafting; multi-walled carbon nanotubes